Impact of diet and vitamins on Mental Health - A systematic review - Cichowska, Zuzanna; Kiereta, Kacper; Rdzanek, Bartłomiej Józef; Głodowska, Klaudia; Chmielowiec, Laura; Bacik, Małgorzata; Żelazo, Jakub; Wacławek, Katarzyna; Janawa, Kamil; Ciesielka, Anna; et al. (Quality in Sport, 2025)
The process of determining risk factors and direct causes that contributed to the development of mental health disorders is not yet completely understood and it is considered multifactorial. Numerous studies have examined the correlation between lifestyle factors, health habits, vitamin levels or consumed supplements with the development of depression. Therefore, observed associations established the importance of dietary patterns, deficiencies of vitamin D or B-complex vitamins (B6, B9, B12) in patients with depressive symptoms. Moreover, these vitamins are involved in essential neurobiological processes such as neurotransmitter synthesis, homocysteine metabolism, neuroinflammation regulation, and oxidative stress reduction. Studies have also shown that the supplementation of the essential nutrients provide promising benefits and may improve the quality of life and well-being. Acknowledging the nutritional impact on mental health can contribute to a better understanding of its etiology and plan more effective treatment strategies.